2010
DOI: 10.1002/jhm.849
|View full text |Cite
|
Sign up to set email alerts
|

Making inpatient medication reconciliation patient centered, clinically relevant and implementable: A consensus statement on key principles and necessary first steps

Abstract: Executive Summary: Medication errors and adverse events caused by them are common during and after a hospitalization.The impact of these events on patient welfare and the financial burden, both to the patient and the healthcare system, are significant. In 2005, The Joint Commission put forth medication reconciliation as National Patient Safety Goal (NPSG) No. 8 in an effort to minimize adverse events caused during these types of care transitions. However, the meaningful and systematic implementation of medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 14 publications
3
140
0
7
Order By: Relevance
“…Patient counselling is a key component of this process, providing an opportunity to inform patients of new medications, treatment modifications, and drug administration schedules [2,8,9]. Studies have shown that the reconciliation process of gathering, organising, and communicating medication information is time-consuming and can be affected by several factors [10], among which are the large number of professionals involved in the process, including clinicians, hospital pharmacists, nurses, general practitioners (GP), community pharmacists, and community caregivers [11][12][13]. A lack of communication, understanding, and collaboration between hospital and community caregivers also represents a significant barrier to successful implementation of a MedRec process [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Patient counselling is a key component of this process, providing an opportunity to inform patients of new medications, treatment modifications, and drug administration schedules [2,8,9]. Studies have shown that the reconciliation process of gathering, organising, and communicating medication information is time-consuming and can be affected by several factors [10], among which are the large number of professionals involved in the process, including clinicians, hospital pharmacists, nurses, general practitioners (GP), community pharmacists, and community caregivers [11][12][13]. A lack of communication, understanding, and collaboration between hospital and community caregivers also represents a significant barrier to successful implementation of a MedRec process [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Previous attempts to share responsibility for medication reconciliation have divided this collaborative work into an ineffective series of discrete tasks. 7 In a typical medication reconciliation process, nurses list current medications, physicians prescribe while referencing the list, and pharmacists periodically evaluate overall medication use. It isn't uncommon for one or more of these discrete tasks to be left incomplete or unintentionally duplicated.…”
Section: Nurse-pharmacist Partnersmentioning
confidence: 99%
“…La conciliation doit être intégrée à la démarche qualité de l'établissement. Des indicateurs doivent être définis et suivis régulièrement pour évaluer l'impact de la conciliation sur les erreurs médicamenteuses et montrer son utilité en matière de sécurité des patients [34]. Le développement dans les établissements de santé français de la conciliation médicamenteuse sera probablement facilité par l'utilisation des nouvelles technologies de l'information et des communications.…”
Section: Article Originalunclassified